2021
DOI: 10.1002/adfm.202105717
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Hydrated Gel Electrolyte for Long‐Cycling Zn‐Ion Battery with NASICON‐Type Cathode

Abstract: Aqueous Zn-ion batteries are promising and safe energy storage technologies. However, current aqueous electrolyte Zn-ion battery technology is hindered by undesirable reactions between the electrolyte and electrodes, which can lead to Zn dendrite growth, gas evolution, and cathode degradation. In this study, a hydrated gel electrolyte (HGE) that combines adiponitrile (ADN) and Zn(ClO 4 ) 2 •6H 2 O in a polymeric framework is created. ADN is found to stabilize the interface between the electrolyte and anode/cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…[ 7 ] However, parasitic reactions at the interface between Zn metal anodes (ZMAs) and AEs, such as the uncontrolled growth of dendrites, H 2 evolution, corrosion, and passivation, cause ZMAs to degrade, limiting the commercializability of ZIBs. [ 8–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] However, parasitic reactions at the interface between Zn metal anodes (ZMAs) and AEs, such as the uncontrolled growth of dendrites, H 2 evolution, corrosion, and passivation, cause ZMAs to degrade, limiting the commercializability of ZIBs. [ 8–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…This is thanks to the strong H‐bond interactions among eutectic composition and gel/polymer network, further suppressing water reactivity and reinforcing the stability of SSEs. [ 82 ]…”
Section: Eutectic Electrolytes For Diverse Rzb Applicationsmentioning
confidence: 99%
“…is thanks to the strong H-bond interactions among eutectic composition and gel/polymer network, further suppressing water reactivity and reinforcing the stability of SSEs. [82] Interestingly, Cai et al recently revealed a water-salt oligomers electrolytes (WSOEs) that formed without adding additional monomers, the super-solubility (up to 75 m) of ZnCl 2 /ZnBr 2 /Zn(OAc) 2 aqueous electrolyte is attributed to the formation of acetatecapped bridging via Br − /Cl − …H and Br − /Cl − /O…Zn 2+ interactions. As a result, this super-soluble electrolyte exhibits a polymer-like glass transition temperature around −70 °C and enables high-performance with a reversible capacity (605.7 mAh g −1 ) and a CE of 98.07% (Figure 8a).…”
Section: Solid-state Eutectic Electrolytesmentioning
confidence: 99%
“…[27][28][29] Table 1 shows the reported electrolyte designs to improve the narrow ESW of aqueous electrolytes. [30][31][32][33][34][35][36][37][38][39][40][41] Herein, we discuss strategies to suppress water decomposition for the broad ESW of aqueous electrolytes and high operating voltage in ZIBs, including the optimization of pH, utilization of bication electrolytes, introduction of small-dipole additives, and design of polymer-supported gel electrolytes.…”
Section: Electrolyte Modification For High Voltage Zinc-ion Batteriesmentioning
confidence: 99%
“…The poly(ethylene glycol) dimethacrylate (PEGDM)-based structure assisted the formation of gel electrolytes with a strong hydrogen bonding. [39] The designed HGE exhibited numerous advantages for use in aqueous ZIBs, such as low manufacturing cost, safety, mechanical flexibility, the high solubility of Zn(ClO 4 ) 2 salt, the utilization of adiponitrile (AND) as an organic solvent molecule for the large ESW, and electrochemical/thermal stability. In particular, the OER potential shifted from 2.53 to 2.63 V (vs. Zn/ Zn 2 + ) in the optimized 2 M Zn(ClO 4 ) 2 -based HGE electrolyte (Figure 3b).…”
Section: Gel Electrolytesmentioning
confidence: 99%